Irinotecan and temozolomide in recurrent Ewing sarcoma: an analysis in 51 adult and pediatric patients. (3rd July 2018) - Palmerini, E.; Jones, R. L.; Setola, E.; Picci, P.; Marchesi, E.; Luksch, R.; Grignani, G.; Cesari, M.; Longhi, A.; Abate, M. E.; Paioli, A.; Szucs, Z.; et al.
Abstract: Background: Data on temozolomide (TEM) and irinotecan (IRI) activity in recurrent Ewing sarcoma (EWS), especially in adult patients, are limited. Methods : Patients receiving TEM 100 mg/m 2 /day oral, and IRI 40 mg/m 2 /day intravenous, days 1–5, every 21 days, were included in this multi-institutional retrospective study. Disease control rate (DCR) [overall response rate (ORR) [complete response (CR) + partial response (PR)] + stable disease (SD)], 6-months progression-free survival (6-mos PFS) and 1-year overall survival (OS) were assessed. Results : The median age of the 51 patients was 21 years (range 3–65 years): 34 patients (66%) were adults (≥18 years of age), 24 (48%) had ECOG 1 and 35 (69%) were presented with multiple site recurrence. TEMIRI was used at first relapse/progression in 13 (25%) patients, while the remainder received TEMIRI for second or greater relapse/progression. Fourteen (27%) patients had received prior myeloablative therapy with busulfan and melphalan. We observed five (10%) CR, 12 (24%) PR and 19 (37%) SD, with a DCR of 71%. 6-mos PFS was 49% (95% CI 35–63) and it was significantly influenced by ECOG (6-mos PFS 64% [95% CI 45–83] for ECOG 0, 34% [95% CI 14–54] for ECOG ≥1; p  = .006) and LDH (6-mos PFS 62% [95% CI 44–79] for normal LDH, 22% [95% CI 3–42] for high LDH; p  = .02), with no difference according to line of treatment, age and metastatic pattern. One-year OS was 55% (95% CI 39–70), with RECIST response ( p  = .001) and ECOG ( p  = .0002) independently associated with outcome. Grade 3 and 4 toxicity included neutropenia in 12% of patients, thrombocytopenia in 4%, diarrhea in 4%. Conclusions: This series confirms the activity of TEMIRI in both adults and pediatric patients. This schedule offers a 71% DCR, independently of the line of chemotherapy. Predictive factors of response are ECOG and LDH.